Ligand-Mediated Endocytosis and Trafficking of the Insulin-Like Growth Factor Receptor I and Insulin Receptor Modulate Receptor Function - Morcavallo, Alaide; Stefanello, Manuela; Iozzo, Renato V.; Belfiore, Antonino; Morrione, Andrea (Frontiers in Endocrinology, 2014)
The insulin-like growth factor (IGF-I) system and its two major receptors, the IGF-IR and IR, plays a central role in a variety of physiological cellular processes including growth, differentiation, motility and glucose homeostasis. The IGF-IR is also essential for tumorigenesis through its capacity to protect cancer cells from apoptosis. The IR is expressed in two isoforms: the IR isoform A (IR-A) and isoform B (IR-B). While the role of the IR-B in the regulation of metabolic effects has been known for several years, more recent evidence suggests that the IR, and in particular the IR-A, may be involved in the pathogenesis of cancer. Ligand-mediated endocytosis of tyrosine-kinases receptors plays a critical role in modulating the duration and intensity of receptors action but while the signaling pathways induced by the IGF-IR and IR are quite characterized, very little is still known about the mechanisms and proteins that regulate ligand-induced IGF-IR and IR endocytosis and trafficking. In addition, how these processes affect receptor downstream signaling has not been fully characterized. Here we discuss the current understanding of the mechanisms and proteins regulating IGF-IR and IR endocytosis and sorting and their implications in modulating ligand-induced biological responses.